The reconstitution of SDRs: Procedure and proposal for modification - Rolf M. Jeker (Intereconomics, 1978)
Among the various limitations put by the IMF on the free use of Special Drawing Rights (SDRs) is the reconstitution requirement which binds participants in the Special Drawing Account to maintain a stipulated average level of allocated SDRs. Using the example of Zambia which is representative for many developing countries, this article displays the adverse effects which arise from the present reconstitution rules and proposes a possible modification.
Keywords: 330; IMF